Keautentikan Naskah (Teks) Ṣahifah Madinah Dalam Perspektif Hadis - Hemawati Hemawati (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Sahifah Medina provides a very important teaching related to state life exemplified by the Prophet SAW. The Sahifah of Medina is considered the hadith. Regarding the validity of the Sahifah Medina manuscript, it is still doubted by some people. Therefore, it is feasible and very important to look for sources of hadis Sahifah Medina. The purpose of this study was to find out the source of the Hadith of the Sahifah of Medina and to know the authenticity of the manuscript (text) of the Sahifah of Medina. To conduct this research, the researcher uses a library research approach. The results showed that the authenticity of the text of ahifah al-Madinah, was born from the words of the prophet's actions and taqrir, because ahifah Medina was the result of the actions of the prophet, it can be said that the text of ahifah Medina is Hadit. It can also be seen that there is support that strengthens the truth, including the Hadith in Sahih Bukhari, Sahih Muslim, Sunan at-Tirmidhi, Sunan Abu Daud and also from Imam Ahmad. The existence and truth of the Sahifah al-Madinah manuscript (text) was found only in two places, namely from the book of Al Amwal and the book of sirah nabawiyah Ibn Hisham. However, there are no Hadiths containing the text of the Sahifah of Medina as a whole in the well-known Hadith books.The entire contents of the Sahifah of Medina are contained in the Hadiths of the Prophet PBUH, but the entire text of the Sahifah of Madinah, is not found in the standard Hadith books. Because of the narration there is no element of companions and there are 2 narrators who are da'if and the sanad is broken at the level of friends (mursal sahabi). However, due to the existence of the Sahifah of Medina in the sirah nabawiyah of Ibn Hisham and the hadiths that contain the contents of the Sahifah of Medina partially, the authenticity of the Sahifah of Medina can be accepted